Performance recording of sheep in the Sudan. 1. Reproductive traits - El-Amin, F.M. (1984)
This study reports on a 2 year observation on some reproductive traits of Desert sheep at Khartoum, Sudan. Data on duration of oestrous and pregnancy, seasonality of lambing, ewe fertility and reproductive rate, birth weight, prenatal and preweaning mortality rate, and sex ratio included.